Understanding respiratory syncytial virus (RSV) vaccine development and aspects of disease pathogenesis. (1st February 2016) - Jorquera, Patricia A.; Anderson, Lydia; Tripp, Ralph A.
ABSTRACT: Respiratory syncytial virus (RSV) is the most important cause of lower respiratory tract infections causing bronchiolitis and some mortality in young children and the elderly. Despite decades of research there is no licensed RSV vaccine. Although significant advances have been made in understanding the immune factors responsible for inducing vaccine-enhanced disease in animal models, less information is available for humans. In this review, we discuss the different types of RSV vaccines and their target population, the need for establishing immune correlates for vaccine efficacy, and how the use of different animal models can help predict vaccine efficacy and clinical outcomes in humans.